(untitled) (Journal of Intellectual Disability - Diagnosis and Treatment, 2019)
Breast cancer is the most common cancer and a common cause of death, which occurs due to cancer among women in the world. Cancer cells need a lot of energy to their uncontrolled growth, so it seems that the expression of the enzyme in the Krebs cycle is changing. There are some reports about mutations and altered expression of succinate dehydrogenase, fumarate Hydratase, and isocitrate dehydrogenase in human cancers. This research aimed to investigate the role of magnetite nanoparticle Oleuropein on the Krebs cycle proteins expression on the breast cancer cell line. Oleuropein is one of the polyphenolic components in olive trees and has some benefits in some diseases, including cancer. In addition to testing the viability test MTT (3- 4,5 Dimethylthiazol-2-yl -2,5-diphenyltetrazolium bromide) assay, in three levels of Oleuropein 0ppm, 300ppm, 600ppm proteomics analysis was also performed in cell line MCF7 in this study. The results of differential protein spots identification into two-dimensional electrophoresis and matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MS-MALDI-TOF-TOF), showed that fumarylacetoacetate hydrolase, succinate-coenzyme A ligase and isocitrate dehydrogenase1 are differential proteins upregulated after treated with 300ppm and 600ppm of oleuropein. It seems that Nano Oleuropein is a booster of Krebs cycle with upregulation of Fumarylacetoacetase, succinate-CoA ligase, and isocitrate dehydrogenase1. Uncoordinated Overexpression of some Krebs cycle protein can be one of the inhibition mechanisms on the breast cancer cell line under Oleuropein treatment.